Process, Strategy, and Contextual: The Deadlock Situation in The Negotiation for Resolving Conflict Between Russia and Ukraine (2022-2025) - Dedi Yusuf; R. Widya Setiabudi Sumadinata; Akim (Yayasan Ilomata, 2026)
The conflict between Russia and Ukraine escalated into a full-scale war following Russia’s invasion of Ukraine in 2022. Since then, both parties have engaged in several negotiation efforts aimed at resolving the conflict. However, from all those negotiations conducted none of them produce any agreement or any framework to resolve the conflict. This is seen by the researcher as a deadlocked situation within the negotiation. By using qualitative descriptive research with document analysis using Faure’s deadlock within negotiation framework, this research indicates that negotiation between Russia and Ukraine for resolving their conflict has reached a deadlocked situation. This research also found that several factors such as process, strategy, and contextual factor that are contributing to the deadlock situation within the negotiation. The findings suggest that these factors are creating a condition where during negotiations strategies adopted by both countries during negotiation and social, political, and legal pressure from within the countries makes them have very little maneuver during the negotiation, which creates a lack of any substantial agreement from the negotiation to resolve the conflict. This research contributes to the limited amount of discourse regarding the negotiation conditions that occurred between Russia and Ukraine for resolving their conflict, offering a new perspective by applying Faure’s indicators and factors such as Process, Strategy, and Contextual towards this issue.